2021
DOI: 10.1186/s12886-021-02160-6
|View full text |Cite
|
Sign up to set email alerts
|

Changes of macular vessel density and thickness in gas and silicone oil tamponades after vitrectomy for macula-on rhegmatogenous retinal detachment

Abstract: Purpose To investigate the macular vessel density and thickness in macular-on rhegmatogenous retinal detachment (RRD) after vitrectomy with gas and silicone oil (SO) tamponade. Methods Patients with macular-on RRD eyes, treated with a single successful vitrectomy with gas or SO tamponade and a minimum 30 months follow-up, were reviewed. Best-corrected visual acuity (BCVA), macular vessel density and retinal thickness by using optical coherence tomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 41 publications
4
9
0
Order By: Relevance
“…Regarding the effects on full retinal thickness and thickness between the inner limiting membrane and inner plexiform layer, SO had more negative tamponade effects than Gas, with no statistically significant intergroup differences. These trends were almost consistent with previous studies in RRD eyes (Inan et al, 2020;Zhou et al, 2020;Liu et al, 2021), although the etiology and mechanisms of RRD and PDR were quite different.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Regarding the effects on full retinal thickness and thickness between the inner limiting membrane and inner plexiform layer, SO had more negative tamponade effects than Gas, with no statistically significant intergroup differences. These trends were almost consistent with previous studies in RRD eyes (Inan et al, 2020;Zhou et al, 2020;Liu et al, 2021), although the etiology and mechanisms of RRD and PDR were quite different.…”
Section: Discussionsupporting
confidence: 92%
“…A retrospective study completed by Inan et al (2020) found thinning in the layers of the ganglion cell layer, outer plexiform layer, and outer nuclear layer in the SO group. Moreover, Liu et al (2021) reported that the parafoveal vessel densities in the SVC and the corresponding inner retinal thickness were significantly reduced in the affected eyes compared to the contralateral eyes in the SO group but similar between the affected eyes and the contralateral eyes in the Gas group. These studies suggest that the use of SO tamponade affects retinal layer thickness more significantly than perfluoropropane gas tamponade in eyes with RRD.…”
Section: Discussionmentioning
confidence: 91%
“…In detail, the multivariate regression analyses showed that only the type of tamponade was significantly correlated with the final BCVA in the Macula-ON group, as eyes filled with gas had a better final BCVA then those filled with SO and this is in line with some previous studies [ 13 , 14 ].…”
Section: Discussionsupporting
confidence: 89%
“…On the one hand, it has been hypothesized that the SCP and the superficial retinal layers, being in contact with SO, could be more susceptible to potential SO-related mechanical/cytotoxic damage [ 159 ]; on the other hand, the DCP is considered more susceptible to ischemic damage due to its intraretinal location [ 162 ]. In addition, Liu et al [ 163 ] speculated that the superficial vascular changes might also be related to the elevation of IOP as they found a decreased parafoveal SCP VD only in eyes that had experienced raised IOP during the follow-up. It has to be highlighted that most of the studies evaluating SO-related changes on OCTA have been performed in eyes treated for macula-off RD and, thus the results have to be interpreted with caution.…”
Section: Retinal Changes Associated With Silicone Oilmentioning
confidence: 99%
“…Indeed, the macular detachment itself may induce macular vascular changes in up to 71.1% of cases in the absence of SO endotamponade [ 164 ]. However, a lower parafoveal VD in the superficial capillary plexus (SCP) has been reported when comparing SO-filled eyes with air-filled after macula-off RD repair [ 159 ] and gas-filled eyes after macula-on RD repair [ 163 ]; this may support a specific role of SO in macular microvasculature effects. Moreover, the nasal sector and the FAZ of DCP may be more impaired in case of macular detachment [ 161 ].…”
Section: Retinal Changes Associated With Silicone Oilmentioning
confidence: 99%